Spatiotemporal evolution and trade-offs among ecosystem services in Tianjin Wetland nature reserves based on the InVEST model - Yue, Ang; Guo, Xueer; Gong, Haiying; Ji, Xinhui; Zhang, Yatao; Wang, Wanfeng (Frontiers in Environmental Science, 2025)
Wetland ecosystem nature reserves provide both ecological protection and cultural-educational functions, requiring scientific evaluation of their ecosystem services and interactions. This study assessed water resource supply, soil conservation, carbon fixation and oxygen release, and habitat quality in four wetland reserves in Tianjin from 2000 to 2020 using the InVEST model. Spatial and temporal dynamics were examined, and trade-offs and synergies among services were analyzed using an ecosystem service trade-off synergy model. Results showed that: (1) ecosystem service functions varied significantly across reserves. Habitat quality improved, soil conservation declined slightly, and carbon storage decreased from 7.61 t/hm2 in 2000 to 5.23 t/hm2 in 2015, then rebounded. (2) Core and buffer zones generally had higher service levels than experimental zones, with carbon storage and soil retention higher by approximately 1 t/hm2 and 0.1 t/hm2, respectively. (3) Soil conservation showed strong synergy with habitat quality and carbon storage, while carbon storage exhibited trade-offs with habitat quality and water yield. These findings provide a scientific basis for targeted management of wetland reserves.